Prevention of Postoperative Venous Thrombosis: A Randomized Trial Comparing Unfractionated Heparin with Low Molecular Weight Heparin in Patients Undergoing Total Hip Replacement - Planes, Andrè; Vochelle, Nicole; Mazas, Frçngois; Mansat, Christian; Zucman, Jean; Landais, Alain; Pascariello, Jean Claude; Weill, Dan; Jean, Butel (Thrombosis and Haemostasis, 1988)
A double blind randomized trial comparing subcutaneous enoxaparin (40 mg once daily) with standard unfractionated calcium heparin administered at a dose of 5,000 units every 8 hours in patients undergoing elective hip replacement has been performed. Treatment regimens began 12 hours preoperatively with enoxaparin, 2 hours preoperatively with standard unfractionated calcium heparin, and were continued for 15 days or until discharge. Venography was performed in all patients. Two hundred thirty-seven patients were included in the study: 113 received unfractionated heparin and 124 received enoxaparin. The incidence of proximal deep vein thrombosis was reduced from 18.5% in the unfractionated heparin group to 7.5% in the enoxaparin group (p = 0.014), and the incidence of total deep vein thrombosis was similarly reduced from 25% to 12.5% (p = 0.03). There were two major bleeding episodes and one minor bleed in the enoxaparin group compared to two minor bleeds in the unfractionated heparin group. Patients who received enoxaparin required fewer red blood cell transfusions and had a significantly higher hemoglobin on postoperative days 3 and 4. Thus prophylaxis with enoxaparin, 40 mg once daily, is simple, safe and more effective than standard low dose unfractionated heparin in preventing deep vein thrombosis in patients undergoing elective hip replacement.
Keywords: Low molecular weight heparin; Postoperative thrombosis; Total hip replacement